Development of Cost-Effective Fuel Briquette with Poultry Manure - Shams, S M Nasif; Hasan, A M Mahmudul; Bony Amin, Shams Bin; Mazumder, Gour Chand (Dhaka University Journal of Science, 2023)
Biomass can be converted into either heat energy or electrical or energy carriers using both thermo-chemical and bio-chemical conversion. Briquetting is a process where untreated biomass is converted into homogeneous, uniformly sized high density solid blocks. Briquettes are used in boilers, heating plants, thermal power stations and by individual households for heating. Present study focuses on using poultry manure with rice husk and saw dust. Poultry manure mixed with rice husk or saw dust by 60:40 ratio provides comparatively higher bond strength. Calorific value varies significantly with the use of poultry manure and tree leaves as well as its production cost. Pure rice husk contains higher calorific value (HCV) 12.6 MJ/Kg where adding poultry manure reduces its value to 10.3 MJ/Kg and Saw dust shows 10.4 MJ/Kg where pure saw dust has 16.3 MJ/Kg in 60:40 ratios with poultry manure. Addition of 20% tree leaves on weight basis ratio of 40:40:20 with base materials and poultry manure shows 10.5 MJ/Kg and 11.7 MJ/Kg respectively for rice husk and saw dust. Competitive price of briquette for 60:40 ratios with Poultry Manure shows 6 BDT/Kg and 5BDT/Kg when secondary material is added. Moreover, if the machine capacity increases the price is reduced. Dhaka Univ. J. Sci. 71(2): 95-103, 2023 (July)